Exploring the antibacterial property of silver nanotriangles synthesized using biocompatible polymers - Shroff, Sailee (2018)
Medical devices contaminated with pathogens are the most common source of hospital acquired infections. To prevent the spreading of the infections to other patients and to ensure the safety of the medical devices, hospitals undertake obligatory decontamination procedures. The current decontamination procedures use expensive and hazardous disinfectants and lengthy sterilization protocols. Some bacteria have also developed resistant strains against common disinfectants, as well as against antibiotics of a similar structures through the process of cross resistance. Thus, there is an emerging need for the development of an alternate class of antibacterial agents that can be coated on all categories of medical devices and are active against a broad range of pathogens. Studies on silver nanoparticles in the past have highlighted their antibacterial nature, but toxicity associated with metallic silver has limited its applicability in biomedical science. With a future aim of developing an antibacterial coating for medical devices that overcomes all the above problems, we synthesized silver nanotriangles using biocompatible polymers like polyethylene glycol (PEG) and poly(sodium) styrene sulphonate (PSSS). The use of biocompatible polymers as a surface coating is hypothesized to reduce the cytotoxicity associated with the nanoparticle. Nanotriangles were of particular interest to us due to their high reactivity with bacterial surfaces that comes from their pointy vertexes and the presence of large number of high atom density facets such as {111}, which are not present in other shapes such as sphere, rods, etc. Techniques like light spectroscopy and Transmission electron microscopy were used to characterize the nanotriangles. Nanotriangles of PEG were mostly triangular with sharp edges and 35.6 % of them had edge length between 40-50 nm, while the nanotriangles of PSSS were quasi spherical to triangular with blunt edges and 37.5 % of them had edge length between 20-30 nm. The antimicrobial effect of nanotriangles of PEG and PSSS on bacteria were examined using agar plates and liquid cultures of Escherichia coli strain (DH5α). At lower dilution ratios (3/5) of PEG and PSSS nanotriangles, a clear antibacterial effect was observed, whereas, higher dilution ratios (1/10) only revealed a reduction in growth of the E. coli cells. With these set of results, silver nanotriangles made using biocompatible polymers provides innovative prospects in being used as a future antibacterial coating for medical devices.